Green Training and Innovation in Giriloyo Batik MSMEs: The Roles of Green Culture, Human Capital - Naili Fithriyah; Muafi Muafi (Penerbit Goodwood, 2025)
Purpose: This study examines the effect of Green Training (GT) on Green Innovation (GI) by incorporating the mediating roles of Green Organizational Culture (GOC) and Green Human Capital (GHC) in batik micro, small, and medium enterprises (MSMEs) located in Giriloyo, Bantul, DIY. Research Methodology: A quantitative research design was employed using a survey method. Data were collected through structured questionnaires distributed to owners and employees of batik MSMEs in Giriloyo. The collected data were analyzed using partial least squares–structural equation modeling (PLS-SEM) to test the direct and mediating relationships among variables. Results: The results indicate that Green Training has a positive and significant effect on Green Organizational Culture and Green Human Capital. Furthermore, both GOC and GHC significantly mediate the relationship between GT and green innovation, indicating that green-oriented internal capabilities play a crucial role in transforming training initiatives into sustainable innovation outcomes. Conclusions: This study confirms that effective green training enhances environmentally oriented organizational culture and strengthens green-related human capital, which in turn fosters green innovation among batik MSMEs. Limitations: This study was limited to batik MSMEs in Giriloyo, Bantul, which may constrain the generalizability of the findings to other sectors or regions. Contributions: This research contributes to green human resource management (GHRM) literature by clarifying the mechanisms through which GT influences green innovation. Practically, it offers insights for batik MSMEs in designing sustainability-oriented human resource development strategies.